Carbon nano diaphragm material and lithium ion battery

By using carbon nanotube/Zr-mofs composite coating layer in lithium battery separators, the problems of insufficient mechanical strength and ion conductivity of traditional separators are solved, and efficient ion transmission and battery performance are achieved.

CN120272114APending Publication Date: 2025-07-08AGA TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510427288.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2025-07-08

AI Technical Summary

Technical Problem

Traditional lithium battery separators have limitations in mechanical strength, thermal stability and ion conductivity, resulting in low ion transmission rate and affecting charge and discharge efficiency.

Method used

The carbon nanotube/Zr-mofs composite material is used as the coating layer, and the composite of amide-modified carbon nanotubes and zirconium-based organic frame material is improved to improve the porosity and wetting performance of the membrane, provide a large number of ion channels, and enhance mechanical properties and insulation.

Benefits of technology

The ion conductivity and wetting performance of lithium batteries are improved, ensuring that the electrolyte is fully in contact with the separator, and improving the charging and discharging efficiency and battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a carbon nano diaphragm material and a lithium ion battery, and relates to the technical field of battery diaphragms, the carbon nano diaphragm material comprises the following components: a carbon nanotube / Zr-mofs composite material, a dispersant, a thickener, an adhesive and a wetting agent; the preparation method of the carbon nanotube / Zr-mofs composite material comprises the following steps: preparing an amide modified carbon nanotube; dissolving a zirconium salt compound into water to obtain a first solvent, adding the amide modified carbon nanotubes into a buffering agent, uniformly dispersing the amide modified carbon nanotubes to obtain a second solvent, and mixing the first solvent and the second solvent to obtain a mixture; heating the mixture to obtain a gel product; and centrifugally separating the gel product, washing with water, drying and grinding to obtain the carbon nanotube / Zr-mofs composite material. The carbon nano tube / Zr-mofs composite material has relatively high porosity and relatively good infiltration performance, and the ionic conductivity of the diaphragm is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery separators, and in particular to a carbon nanotube separator material and a lithium-ion battery. Background Art

[0002] With the rapid development of new energy technologies, lithium batteries, as an efficient and environmentally friendly energy storage solution, have been widely used in fields such as electric vehicles and energy storage systems. The separator is a key component in lithium batteries, and its performance directly affects the safety, capacity, and cycle life of the battery. Traditional separator materials have certain limitations in terms of mechanical strength, thermal stability, and ionic conductivity, and it is difficult to meet the requirements of high-performance lithium batteries.

[0003] The published invention patent number CN116190922A discloses a carbon nanotube composite-coated lithium-ion battery separator and its preparation method. The separator includes a base film and a coating layer adhered to one or both film surfaces of the base film. The base film is a polyolefin film, and the coating layer contains a carbon nanotube composite coated with BaSO4 and Al(OH)3, a dispersant, a thickener, an adhesive, and a wetting agent. In the lithium-ion battery separator obtained in the present invention, due to the addition of BaSO4 with good high-temperature resistance and thermal conductivity, and Al(OH)3 with flame retardant properties, the carbon nanotubes increase the mechanical properties of the material on the one hand and enhance the electrical conductivity of the material on the other hand, which is beneficial to enhancing the rapid transmission of lithium ions. The synergistic effect of the three greatly improves the electrical conductivity, mechanical strength, and thermal shrinkage performance of the separator. However, due to the poor wettability of BaSO4 and Al(OH)3 to the electrolyte, the wettability of the separator is weak, resulting in a decrease in the ion transport rate of the separator and being unfavorable for the efficient charge and discharge of lithium batteries. Summary of the Invention

[0004] The purpose of the present application is to provide a carbon nanotube separator material and a lithium-ion battery to solve the problem of slow charge and discharge efficiency of lithium batteries due to the low ion transport rate of the separator.

[0005] In the first aspect, a carbon nanotube separator material provided by the present application adopts the following technical solution: A carbon nanotube separator material includes the following components: carbon nanotube / Zr-mofs composite material, dispersant, thickener, adhesive, and wetting agent; The preparation method of the carbon nanotube / Zr-mofs composite material includes the following steps: (1) Prepare amide-modified carbon nanotubes; (2) Dissolve a zirconium salt compound in water to obtain a first solvent, add amide-modified carbon nanotubes to a buffer and disperse them evenly to obtain a second solvent, and mix the first solvent and the second solvent to obtain a mixture; (3) Heat the mixture to obtain a gel product; (4) Centrifuge the gel product, wash it with water, dry it, and grind it to obtain a carbon nanotube / Zr-mofs composite material.

[0006] By adopting the above technical solution, the lithium battery separator needs to enable ions to pass through efficiently while maintaining insulation, so as to ensure the charge and discharge performance of the battery. The insulation of the separator is mainly provided by the base film, while the coating layer can improve the ion conductivity and mechanical properties of the separator. The carbon nanotube / Zr-mofs composite material has a high porosity and good wettability by combining carbon nanotubes and an organic framework material based on zirconium ions, enabling the electrolyte to come into full contact with the separator and providing a large number of ion channels for ions to pass through the separator efficiently, thereby improving the ion conductivity of the separator. Both carbon nanotubes and mof materials have good conductivity and corrosion resistance due to their high specific surface area and good chemical stability. On this basis, after amide modification, the carbon nanotubes and zirconium-based mof materials are compounded, enabling the carbon nanotubes to be connected to the zirconium-based mof through amide groups, so as to be evenly dispersed, avoiding the aggregation of carbon nanotubes. While maintaining the performance stability of the carbon nanotube / Zr-mofs composite material, the problem of weak hydrophilicity of carbon nanotubes is improved, making the carbon nanotube / Zr-mofs composite material have good wettability, and the electrolyte can fully infiltrate the separator, improving the ion conduction performance of the lithium battery.

[0007] Optionally, the mass ratio of the carbon nanotube / Zr-mofs composite material, dispersant, thickener, binder, and wetting agent is between 1:(0.015 - 0.045):(0.010 - 0.035):(0.020 - 0.060):(0.005 - 0.020).

[0008] By adopting the above technical solution, by providing a certain proportion of dispersant, thickener, binder, and wetting agent, the carbon nanotube / Zr-mofs composite material can maintain its performance as a coating slurry and stably cover the surface of the base film, maintaining the structural stability of the separator.

[0009] Optionally, the buffer is selected from one or a mixture of two or more of trimesic acid, terephthalic acid, sodium trimesate, sodium terephthalate, 1,4-naphthalenedicarboxylic acid, and 4,4'-biphenyldicarboxylic acid.

[0010] By adopting the above technical solutions, trimellitic acid, terephthalic acid, sodium trimellitate, sodium terephthalate, 1,4-naphthalenedicarboxylic acid, and 4,4'-biphenyldicarboxylic acid can finely regulate the morphology and structure of MOF during the synthesis process. During the reaction process, the above substances act as templating agents or structure-directing agents, which can affect the growth mode and final morphology of MOF crystals, thereby affecting their performance. In addition, the above substances can also slow down the reaction rate and adjust the acidity and alkalinity of the reaction environment. By making the rate and acid-base environment of the reaction process more stable, it helps the formed carbon nanotube / Zr-mofs composite material to have a more excellent and uniform morphology, thereby improving the performance of the coating slurry.

[0011] Optionally, the zirconium salt compound is selected from one or two of zirconium chloride, zirconium oxychloride, zirconium nitrate, zirconium sulfate, zirconium oxychloride octahydrate, zirconium n-propoxide, zirconium tetraethoxide, zirconium acetate, or zirconocene dichloride.

[0012] By adopting the above technical solutions, the zirconium salt compound can provide zirconium ions for the synthesis process of zirconium-based mof. The zirconium ions and the organic matter are connected by coordination bonds to form a mof material. Zirconium chloride, zirconium oxychloride, zirconium nitrate, zirconium sulfate, zirconium oxychloride octahydrate, zirconium n-propoxide, zirconium tetraethoxide, zirconium acetate, or zirconocene dichloride can easily separate zirconium ions in the reaction environment during the reaction process, maintaining the supply of zirconium ions in the reaction.

[0013] Optionally, in the step (2), the mass ratio of the amide-modified carbon nanotubes to the zirconium salt compound is between (5 - 10):1.

[0014] By adopting the above technical solutions, compared with the zirconium salt compound, the molecular weight of the amide-modified carbon nanotubes is much larger. Therefore, when the mass ratio is relatively large, the ratio of the molecular weights of the two is not much different, and they can be better compounded. Moreover, the mass ratio is more convenient to apply in the actual operation process. The organic solution is mainly used to assist the formation of the composite material to ensure the stable progress of the reaction, and its dosage size.

[0015] Optionally, the preparation of the amide-modified carbon nanotubes includes the following steps: Use an oxidizing agent to oxidize the carbon nanotubes to obtain carboxyl-modified carbon nanotubes; Use an organic amine to perform amidation on the carboxyl-modified carbon nanotubes to obtain amide-modified carbon nanotubes.

[0016] By adopting the above technical solution, the amide-modified carbon nanotubes can improve the wettability of carbon nanotubes and provide sites for synthesizing MOF composites by connecting zirconium ions, enabling the carbon nanotubes to form coordination bonds with zirconium ions through the carbonyl groups on the amide, thereby synthesizing carbon nanotube / Zr-MOF composites. During the amidation process, amide groups cannot be directly introduced onto the surface of carbon nanotubes. Therefore, carboxyl groups are first formed on the surface of carbon nanotubes through an oxidant to obtain carboxyl-modified carbon nanotubes, and then amide-modified carbon nanotubes are obtained by reacting organic amines with the carboxyl-modified carbon nanotubes.

[0017] Optionally, the oxidant is selected from one or a mixture of two of hydrofluoric acid, sulfuric acid, hydrochloric acid, or potassium permanganate; the organic amine is selected from one or more of monomethylamine, dimethylamine, ethylamine, n-propylamine, or isopropylamine.

[0018] By adopting the above technical solution, sulfuric acid, nitric acid, hydrochloric acid, or potassium permanganate can oxidize the carbon atoms in carbon nanotubes into carboxyl groups. By reacting carboxyl groups with simple organic amines with smaller molecular weights, amide groups are connected to the carbon nanotubes, and the other end of the amide group is a smaller molecule, which can avoid destroying the characteristics of the large specific surface area of the amide-modified carbon nanotubes and maintain the performance of the amide-modified carbon nanotubes.

[0019] Optionally, the oxidation treatment specifically includes the following steps: Take carbon nanotubes, add them to the oxidant and disperse evenly, soak for 20 - 30 min, raise the temperature to 60 - 80 °C, keep warm for 5 - 10 h, after cooling to room temperature, wash with water until the solution is neutral, and dry to obtain carboxyl-modified carbon nanotubes; The amidation treatment specifically includes the following steps: Mix carboxyl-modified carbon nanotubes and organic amines in an organic solvent, add 1,3-dicyclohexylcarbodiimide, react at 80 - 90 °C for 8 - 12 h, and after the reaction product is filtered, washed with water, and dried, amide-modified carbon nanotubes are obtained.

[0020] By adopting the above technical solution, infiltrating carbon nanotubes with an oxidant can effectively activate the surface reaction sites of carbon nanotubes and generate intermediate products of partial oxidation reactions. By raising the temperature to the reaction temperature, some carbon atoms in the carbon nanotubes are oxidized into carboxyl groups. The setting of the holding time is to control the number of generated carboxyl groups to control the number of amide groups in the amide-modified carbon nanotubes after amidation. In the amidation reaction, by adding dihydroxyacetone as a catalyst, the hydroxyl groups can react with the amine groups in the organic amines to generate amide groups, obtaining amide-modified carbon nanotubes. The amidation process reacts at a slightly higher temperature for a longer time, which can ensure the full amidation of the hydroxyl groups.

[0021] Optionally, the preparation method of the carbon nanotube diaphragm material includes the following steps: Add carbon nanotube / Zr-mofs composite material and dispersant into deionized water, mix at a rotation speed of 350 - 750 rpm for 30 - 100 min, maintain the rotation speed at 400 - 700 rpm, and sequentially add thickener, binder and wetting agent, with an interval of at least 30 min for each addition. After filtering out iron, a carbon nanotube diaphragm material is obtained.

[0022] By adopting the above technical solution, the dispersant disperses the carbon nanotube / Zr-mofs composite material in the solvent, and while maintaining stirring, the thickener, binder and wetting agent are sequentially added, so that the coating slurry can use the carbon nanotube / Zr-mofs composite material as the main material and have properties such as coating adhesion and curing.

[0023] In the second aspect, a lithium battery provided by the present application adopts the following technical solution: A lithium ion battery includes a diaphragm, and the above carbon nanotube diaphragm material is applied to the diaphragm.

[0024] By adopting the above technical solution, the carbon nanotube diaphragm material prepared by the above solution has better chemical stability and mechanical properties, and at the same time has better ion conductivity and wetting properties, enabling the electrolyte to fully wet the surface of the diaphragm, improving the efficiency of ions passing through the diaphragm during the charge and discharge process, and thus improving the performance of the battery.

[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. The carbon nanotube / Zr-mofs composite material, by combining carbon nanotubes and an organic framework material based on zirconium ions, has a high porosity and good wetting properties, enabling the electrolyte to fully contact the diaphragm and providing a large number of ion channels for ions to efficiently pass through the diaphragm, thereby improving the ion conductivity of the diaphragm. Both carbon nanotubes and mof materials have good conductivity and corrosion resistance due to their high specific surface area and good chemical stability. On this basis, after the carbon nanotubes and zirconium-based mof materials are compounded through amide modification, the carbon nanotubes can be connected to the zirconium-based mof through amide groups, so as to be evenly dispersed, avoid the agglomeration of carbon nanotubes, maintain the performance stability of the carbon nanotube / Zr-mofs composite material, and at the same time improve the problem of weak hydrophilicity of carbon nanotubes, making the carbon nanotube / Zr-mofs composite material have good wettability, enabling the electrolyte to fully wet the diaphragm and improving the ion conduction performance of the lithium battery; 2. During the amidation process, it is impossible to directly introduce amide groups on the surface of carbon nanotubes. Therefore, first, carboxyl groups are formed on the surface of carbon nanotubes through an oxidant to obtain carboxyl-modified carbon nanotubes, and then organic amines are reacted with the carboxyl-modified carbon nanotubes to obtain amide-modified carbon nanotubes; 3. In the amidation reaction, by adding dihydroxyacetone as a catalyst, the hydroxyl group can react with the amino group in the organic amine to form an amide group, thereby obtaining amide-modified carbon nanotubes. The amidation process reacts at a slightly higher temperature for a longer time to ensure sufficient amidation of the hydroxyl group. Detailed implementation mode

[0026] The present application will be further described in detail below with reference to preparation examples, examples and comparative examples.

[0027] In the following preparation examples, examples and comparative examples, the dispersant used is hydrolyzed polymaleic anhydride dispersant; the thickener is sodium carboxymethyl cellulose; the binder is COPNA resin; the wetting agent is a silanol non-ionic surfactant; the buffer is terephthalic acid; the zirconium salt compound is zirconium chloride; the oxidant is a mixed acid formed by sulfuric acid and nitric acid, in which the mass concentration of nitric acid is 65 g / L and the mass concentration of sulfuric acid is 98 g / L, and they are mixed according to the volume ratio of nitric acid to sulfuric acid of 3:1; the organic solvent is dimethylformamide (DMF).

[0028] Preparation Example 1 The preparation of amide-modified carbon nanotubes includes the following steps: S001. Add 450 ml of the mixed acid into a beaker, take 10 g of carbon nanotubes and add them into the mixed acid, soak for 25 min, and during the soaking period, continuously perform ultrasonic dispersion treatment using an ultrasonic instrument. Cover the mouth of the beaker with plastic wrap, raise the temperature to 74 - 76 °C, keep warm for 7 h, and cool to room temperature. After filtering out the reaction product, first wash it with sodium hydroxide solution until the reaction product is neutral, then wash it with ethanol solution, and dry it to obtain carboxyl-modified carbon nanotubes.

[0029] S002. Add 200 ml of dimethylformamide into a beaker, add 10 g of ethylamine and stir until it is dissolved evenly, then add 8 g of the carboxyl-modified carbon nanotubes prepared in step S001, and disperse them evenly using an ultrasonic instrument. Then add 0.6 g of 1,3-dicyclohexylcarbodiimide, and react at 85 °C for 10 h. After the reaction is completed, wait for the reaction product to cool to room temperature, filter out the reaction product, wash it with ethanol solution several times, and dry it to obtain amide-modified carbon nanotubes.

[0030] Preparation Example 2 The preparation of amide-modified carbon nanotubes includes the following steps: S001. Add 450 ml of the mixed acid into a beaker, take 10 g of carbon nanotubes and add them into the mixed acid, soak for 25 min, and during the soaking period, continuously perform ultrasonic dispersion treatment using an ultrasonic instrument. Cover the mouth of the beaker with plastic wrap, raise the temperature to 74 - 76 °C, keep warm for 7 h, and cool to room temperature. After filtering out the reaction product, first wash it with sodium hydroxide solution until the reaction product is neutral, then wash it with ethanol solution, and dry it to obtain carboxyl-modified carbon nanotubes.

[0031] S002. Add 200 ml of dimethylformamide to a beaker, add 10 g of dimethylamine and stir until dissolved evenly. Then add 8 g of the carboxyl group-modified carbon nanotubes prepared in step S001 and disperse evenly using an ultrasonic instrument. Then add 0.6 g of 1,3-dicyclohexylcarbodiimide and react at 85 °C for 10 h. After the reaction is completed, wait for the reaction product to cool to room temperature, filter out the reaction product, wash it several times with ethanol and water, and dry to obtain amide-modified carbon nanotubes.

[0032] Preparation Example 3 The preparation of amide-modified carbon nanotubes includes the following steps: S001. Add 450 ml of mixed acid to a beaker, take 10 g of carbon nanotubes and add them to the mixed acid, soak for 25 min, and during the soaking period, continuously perform ultrasonic dispersion treatment using an ultrasonic instrument. Cover the beaker mouth with plastic wrap, raise the temperature to 74 - 76 °C, keep warm for 7 h, and cool to room temperature. After filtering out the reaction product, first wash it with sodium hydroxide water until the reaction product is neutral, then wash it with ethanol and water, and dry to obtain carboxyl group-modified carbon nanotubes.

[0033] S002. Add 200 ml of dimethylformamide to a beaker, add 10 g of isopropylamine and stir until dissolved evenly. Then add 8 g of the carboxyl group-modified carbon nanotubes prepared in step S001 and disperse evenly using an ultrasonic instrument. Then add 0.6 g of 1,3-dicyclohexylcarbodiimide and react at 85 °C for 10 h. After the reaction is completed, wait for the reaction product to cool to room temperature, filter out the reaction product, wash it several times with ethanol and water, and dry to obtain amide-modified carbon nanotubes.

[0034] Example 1 The preparation method of the carbon nanotube / Zr-mofs composite material includes the following steps: S011. Take 200 ml of deionized water, add 4.6 g of zirconium chloride, mix until dissolved to obtain a first solvent; S012. Take 34.5 g of the amide-modified carbon nanotubes prepared in Preparation Example 1 and disperse them in 300 ml of terephthalic acid to obtain a second solvent; S013. Mix the first solvent obtained in step S011 and the second solvent obtained in S012, and react at 120 °C for 30 h to obtain a gel product; S014. Centrifuge to separate the solid part in the gel product obtained in step S013, and wash it three times with methanol to obtain the carbon nanotube / Zr-mofs composite material.

[0035] Example 2 The preparation method of the carbon nanotube / Zr-mofs composite material includes the following steps: S011. Take 200 ml of deionized water, add 4.6 g of zirconium chloride, and mix until dissolved to obtain the first solvent; S012. Take 23.0 g of the amide-modified carbon nanotubes prepared in Preparation Example 1 and disperse them in 300 ml of terephthalic acid to obtain the second solvent; S013. Mix the first solvent obtained in step S011 and the second solvent obtained in S012, and react at 120 °C for 30 h to obtain a gel product; S014. Separate the solid part in the gel product obtained in step S013 by a centrifuge and wash it three times with methanol to obtain the carbon nanotube / Zr-mofs composite material.

[0036] Example 3 The preparation method of the carbon nanotube / Zr-mofs composite material includes the following steps: S011. Take 200 ml of deionized water, add 4.6 g of zirconium chloride, and mix until dissolved to obtain the first solvent; S012. Take 46.0 g of the amide-modified carbon nanotubes prepared in Preparation Example 1 and disperse them in 300 ml of terephthalic acid to obtain the second solvent; S013. Mix the first solvent obtained in step S011 and the second solvent obtained in S012, and react at 120 °C for 30 h to obtain a gel product; S014. Separate the solid part in the gel product obtained in step S013 by a centrifuge and wash it three times with methanol to obtain the carbon nanotube / Zr-mofs composite material.

[0037] Example 4 Compared with Example 1, the difference is that the amide-modified carbon nanotubes prepared in Preparation Example 2 are used to replace the amide-modified carbon nanotubes prepared in Preparation Example 1.

[0038] Example 5 Compared with Example 1, the difference is that the amide-modified carbon nanotubes prepared in Preparation Example 3 are used to replace the amide-modified carbon nanotubes prepared in Preparation Example 1.

[0039] Application Example 1 The preparation method of the carbon nanotube diaphragm material includes the following steps: Add 120 g of the carbon nanotube / Zr-mofs composite material prepared in Example 1 and 3.6 g of a dispersant to deionized water, mix at a rotation speed of 550 rpm for 60 min, maintain the rotation speed at 400 - 700 rpm, and sequentially add 2.7 g of a thickener, a binder, and a wetting agent, with an interval of at least 30 min between each addition, and obtain the carbon nanotube diaphragm material after filtering out iron.

[0040] The preparation of the lithium-ion battery diaphragm includes the following steps: The carbon nanotube diaphragm material is coated on the base film by a coating process, and after drying at 75 °C, a lithium-ion battery diaphragm is obtained. The coating thickness of the above lithium-ion battery diaphragm is 1.9 - 2.1 μm.

[0041] Application Example 2 Compared with Application Example 1, the difference lies in that the mass of the carbon nanotube / Zr-mofs composite material used is 120 g, the mass of the dispersant is 5.4 g, the mass of the thickener is 4.2 g, the mass of the binder is 7.2 g, and the mass of the wetting agent is 2.4 g.

[0042] Application Example 3 Compared with Application Example 1, the difference lies in that the mass of the carbon nanotube / Zr-mofs composite material used is 120 g, the mass of the dispersant is 1.8 g, the mass of the thickener is 1.2 g, the mass of the binder is 2.4 g, and the mass of the wetting agent is 0.6 g.

[0043] Application Example 4 Compared with Application Example 1, the difference lies in using the carbon nanotube / Zr-mofs composite material prepared in Example 2 to replace the carbon nanotube / Zr-mofs composite material prepared in Example 1.

[0044] Application Example 5 Compared with Application Example 1, the difference lies in using the carbon nanotube / Zr-mofs composite material prepared in Example 3 to replace the carbon nanotube / Zr-mofs composite material prepared in Example 1.

[0045] Application Example 6 Compared with Application Example 1, the difference lies in using the carbon nanotube / Zr-mofs composite material prepared in Example 4 to replace the carbon nanotube / Zr-mofs composite material prepared in Example 1.

[0046] Application Example 7 Compared with Application Example 1, the difference lies in using the carbon nanotube / Zr-mofs composite material prepared in Example 5 to replace the carbon nanotube / Zr-mofs composite material prepared in Example 1.

[0047] Comparative Example 1 Compared with Application Example 1, the difference lies in using an equal mass of carbon nanotubes to replace the carbon nanotube / Zr-mofs composite material prepared in Example 1.

[0048] Comparative Example 2 Compared with Application Example 1, the difference lies in using UIO-66 (a metal-organic framework material formed by self-assembly of zirconium metal centers and terephthalic acid organic ligands) to replace the carbon nanotube / Zr-mofs composite material prepared in Example 1 for testing the ionic conductivity, wettability, and thermal stability of the lithium-ion separator prepared in the application example.

[0049] Ionic conductivity test: At 40 °C, the room-temperature ionic conductivity (unit: S·cm-1) of the composite-coated separator was measured by the AC impedance method. Using metal copper electrodes, first measure the resistance R of the separator in an electrolyte with a volume ratio of 1:1:1 of 1 mol LiPF6 in EC (ethylene carbonate) / DMC (dimethyl carbonate) / EMC (ethyl methyl carbonate). The thickness of the separator is d, and the area of the electrode is S, then

[0050] Wettability test: Punch the prepared battery separator into thin sheets of the same size and weigh them. The mass is recorded as m1. After fully wetting the separator with a conventional lithium-ion battery electrolyte, take it out, wipe off the surface electrolyte and weigh it again. The mass is recorded as m2. Calculate the liquid absorption rate. Liquid absorption rate = (m2 - m1) / m1 * 100%.

[0051] Thermal stability: Punch the separator into thin sheets of the same size for thermal shrinkage test. Record the initial area A1 of the separator before the test. Measure the area A2 of the separator after being placed at 100 °C for 1 h, 150 °C for 1 h, and 200 °C for 1 h respectively. Calculate the thermal shrinkage rate. Thermal shrinkage rate = (A1 - A2) / A1 * 100%.

[0052] Table 1 Performance test results of the lithium-ion battery separators prepared in the application example and the comparative example Combined with Table 1, the application example and the comparative example to explore the performance of the separator coating material prepared in this application.

[0053] Comparing Application Example 1, Application Example 2, and Application Example 3, the difference lies in the proportions of the raw materials in the carbon nanotube separator material. It can be seen that the performance test results of the three are slightly different but not much different, and they all have good performance. It shows that the battery using the separator coating prepared under the condition that the mass ratio of the carbon nanotube / Zr-mofs composite material, dispersant, thickener, binder, and wetting agent is between 1:(0.015 - 0.045):(0.010 - 0.035):(0.020 - 0.060):(0.005 - 0.020) has good ionic conductivity, wettability, and thermal stability.

[0054] Comparing Application Example 1, Application Example 4, and Application Example 5, the difference lies in the raw material ratio of the carbon nanotube / Zr-mofs composite material in the carbon nanotube diaphragm material. It can be seen that the performance test differences among the three are not significant, and they all have good battery performance, indicating that under the condition that the mass ratio of the amide-modified carbon nanotubes to the zirconium salt compound is between (5-10):1, the lithium battery using the prepared diaphragm coating has good ionic conductivity, wettability, and thermal stability.

[0055] Comparing Application Example 1, Application Example 6, and Application Example 7, the difference lies in the selection of raw materials in the carbon nanotube / Zr-mofs composite material in the carbon nanotube diaphragm material. It can be seen that the lithium-ion battery diaphragms prepared in Application Example 1, Application Example 6, and Application Example 7 all have good battery performance, indicating that when the organic amine is selected from ethylamine, dimethylamine, and isopropylamine, the prepared carbon nanotube / Zr-mofs composite material can all have good battery performance.

[0056] Comparing Application Example 1, Comparative Example 1, and Comparative Example 2, the difference is that in Comparative Example 1, carbon nanotubes are used to replace the carbon nanotube / Zr-mofs composite material, and in Comparative Example 2, UIO-66 is used to replace the carbon nanotube / Zr-mofs composite material. It can be seen that compared with Application Example 1, the ionic conductivity and wettability of the battery diaphragms prepared in Comparative Example 1 and Comparative Example 2 have both decreased significantly, and the thermal stability test data has also increased, indicating a decrease in thermal stability. It shows that compared with carbon nanotubes and UIO-66, the lithium-ion battery diaphragm prepared with the carbon nanotube / Zr-mofs composite material as the raw material of the carbon nanotube diaphragm material has more excellent ionic conductivity and thermal stability.

[0057] The embodiments of this specific implementation manner are all preferred embodiments of this application, and do not limit the protection scope of this application accordingly. The same components are denoted by the same reference numerals. Therefore, all equivalent changes made according to the structure, shape, and principle of this application should be covered within the protection scope of this application.

Claims

1. A carbon nanotube diaphragm material, characterized in that, It includes the following components: carbon nanotube / Zr-mofs composite material, dispersant, thickener, binder and wetting agent; The preparation method of the carbon nanotube / Zr-mofs composite material includes the following steps: (1) Prepare amide-modified carbon nanotubes; (2) Dissolve zirconium salt compound in water to obtain the first solvent, add amide-modified carbon nanotubes to the buffer and disperse them evenly to obtain the second solvent, and mix the first solvent and the second solvent to obtain a mixture; (3) Heat the mixture to obtain a gel product; (4) Centrifuge the gel product, wash it with water, dry it and grind it to obtain the carbon nanotube / Zr-mofs composite material.

2. The carbon nanotube diaphragm material according to claim 1, wherein The mass ratio of the carbon nanotube / Zr-mofs composite material, dispersant, thickener, binder and wetting agent is between 1:(0.015 - 0.045):(0.010 - 0.035):(0.020 - 0.060):(0.005 - 0.020).

3. The carbon nanotube diaphragm material according to claim 1, wherein The buffer is selected from one or a mixture of two or more of trimellitic acid, terephthalic acid, sodium trimellitate, sodium terephthalate, 1,4-naphthalenedicarboxylic acid and 4,4'-biphenyldicarboxylic acid.

4. The carbon nanotube diaphragm material according to claim 1, characterized in that, The zirconium salt compound is selected from one or two of zirconium chloride, zirconium oxychloride, zirconium nitrate, zirconium sulfate, zirconium oxychloride octahydrate, zirconium n-propoxide, zirconium tetraethoxide, zirconium acetate or zirconocene dichloride.

5. The carbon nanotube diaphragm material according to claim 1, characterized in that, In the step (2), the mass ratio of the amide-modified carbon nanotubes to the zirconium salt compound is between (5 - 10):

1.

6. The carbon nanotube diaphragm material according to claim 1, wherein The preparation of the amide-modified carbon nanotubes includes the following steps: Use an oxidant to oxidize the carbon nanotubes to obtain carboxyl-modified carbon nanotubes; Use an organic amine to carry out amidation treatment on the carboxyl-modified carbon nanotubes to obtain amide-modified carbon nanotubes.

7. The carbon nanotube diaphragm material according to claim 6, characterized in that, The oxidant is selected from one or a mixture of two of hydrofluoric acid, sulfuric acid, hydrochloric acid or potassium permanganate; the organic amine is selected from one or more of methylamine, dimethylamine, ethylamine, n-propylamine, isopropylamine.

8. According to claim 6 of the carbon nanotube diaphragm material, it is characterized in that The oxidation treatment specifically includes the following steps: Take carbon nanotubes, add them to the oxidant and disperse them evenly, soak for 20 - 30 min, raise the temperature to 60 - 80 °C, keep warm for 5 - 10 h, after cooling to room temperature, wash with water until the solution is neutral, and dry to obtain carboxyl-modified carbon nanotubes; The amidation treatment specifically includes the following steps: Mix carboxyl-modified carbon nanotubes and organic amine in an organic solvent, and add 1,3-dicyclohexylcarbodiimide, react at 80 - 90 °C for 8 - 12 h, after the reaction product is filtered, washed with water and dried, amide-modified carbon nanotubes are obtained.

9. The carbon nanotube diaphragm material according to claim 1, characterized in that The preparation method of the carbon nanotube diaphragm material includes the following steps: Add the carbon nanotube / Zr-mofs composite material and the dispersant to deionized water, mix at a rotation speed of 350 - 750 rpm for 30 - 100 min, maintain the rotation speed at 400 - 700 rpm, and sequentially add the thickener, binder and wetting agent, with an interval of at least 30 min for each addition, and obtain the carbon nanotube diaphragm material after filtering out iron.

10. A lithium-ion battery, characterized in that, Comprising a diaphragm, the diaphragm applying the carbon nanotube diaphragm material according to any one of claims 1-9.

Citation Information

Patent Citations

  • Carbon nanowire composite material coated lithium ion battery diaphragm and preparation method thereof

    CN116190922A